Goat-Sheep Livestock Business Development Strategy in Bekasi City - Ridwan Lutfiadi; Haris Budiyono; Ahya Kamilah; Esi Asyani Listyowati (GoAcademica Research & Publishing, 2023)
The social assistance program for raising goats in Bekasi City is an alternative to post-Covid-19 economic recovery which has been given to 100 business groups but after one year there were only 73 active breeders, so it is interesting to study with the aim of knowing internal factors (strengths and weaknesses) and external factors (strengths and threats) in formulating a strategy for developing a goat-sheep business in Bekasi City. A sample of 40 respondents was taken through a purposive sampling approach and data analysis was carried out qualitatively (descriptive business activities and determining alternative strategies), as well as quantitatively through instrument testing, IFE/EFE analysis, SWOT Matrix and QSPM Matrix. The results of the study show that the goat livestock business in Bekasi City is in a weak condition with strategic priorities, namely (1) revitalizing the revolving program by benchmarking to regions that carry out best practices, (2) maximizing the promotion of the revolving grant model with good management by policy makers, (3) strengthening the readiness of beneficiaries in raising goats, and (4) increasing the number of beneficiaries of sheep livestock assistance.